Failure cause analysis of pipes in district heating network during spring and autumn season - Chorzelski, Maciej; Pachocki, Michał (Instal, 2021)
In the article, materials used for district heating carrier pipes and corrosion phenomena are characterized. Causes of pressure pulsations and noise in pipe networks are described. In conclusion, a simplified description of pipeline failure causes (mainly in the transition spring time) is presented